Oscillatory interaction in a Bose-Einstein condensate: collective and topological excitations - Ramos, Edmir Ravazzi Franco (2012)
In this work, we theoretically analyze the behavior of a Bose-Einstein condensate when it is submitted to oscillatory interactions. For that, a homogeneous magnetic field is applied, tuned near a Feshbach resonance, and then it is set to oscillate in time. This variation of the magnetic field causes a scattering length oscillation, which oscillates to interatomic interaction. Thus, we study collective and topological excitations due this oscillation in the interaction. In addition, we have seen a coupling between collective modes as well a dynamical phase transition associated to topological excitation